Fidelity, Male Privilege and the Sanctity of Marriage: Examining the Decriminalization of Adultery in India - Uma, Saumya (Women & criminal justice, 2023)
This article examines the birth, life and death of the criminal law provision on adultery in India through historical, socio-legal, feminist and human rights perspectives. The provision on adultery was struck down as unconstitutional by the Supreme Court of India in 2018. The article analyses the legal developments culminating in the landmark judgment, as well as its aftermath. It addresses, as a central question, the construction of intimate relationships in criminal law, law’s emphasis on and interest in enforcing a monogamous marriage and consequently the non-recognition of sexual autonomy of women within the same. Through an examination of the judicial reasoning, international jurisprudence, established human rights standards and feminist scholarship, the article argues that adultery has no place in criminal law. Further, it argues that family laws must broaden and take into account newer forms of marriage and relationships that defy traditional, hetero-monogamous notions, based on egalitarian and inclusive principles.